Diabetes is associated with atrial fibrillation phenotype, cardiac and neurological comorbidities: insights from the Swiss-AF study. (14th October 2021) - Bano, A; Rodondi, N; Beer, J; Moschovitis, G; Kobza, R; Aeschbacher, S; Baretella, O; Muka, T; Stettler, C; Franco, O; Conte, G; Sticherling, C; et al.
Abstract: Background: Diabetes mellitus is a major risk factor for atrial fibrillation (AF). However, it remains unclear whether individual AF phenotype and related comorbidities differ between AF patients with and without diabetes. Purpose: To investigate the association of diabetes with AF phenotype, cardiac and neurological comorbidities in patients with documented AF. Methods: Participants of the multicenter Swiss-AF study with available data on diabetes and AF phenotype were eligible. The primary outcomes were parameters of AF phenotype, including AF type (paroxysmal vs non-paroxysmal), AF symptoms (yes vs no), and quality of life (assessed by EQ-5D score). The secondary outcomes were cardiac (ie, history of hypertension, myocardial infarction, heart failure) and neurological comorbidities (ie, history of stroke, cognitive impairment). The cross-sectional association of diabetes with these outcomes was assessed using logistic and linear regression. Results were adjusted for age, sex, and cardiovascular risk factors. Results: We included 2411 AF patients (27.4% women; median age, 73.6 years). Diabetes was not associated with non-paroxysmal AF (odds ratio [OR]=1.01; 95% confidence interval [CI]=0.81 to 1.27). Patients with diabetes less often perceived AF symptoms (OR=0.73; CI=0.59 to 0.91), but had worse quality of life (predicted mean difference in EQ-5D score: β=−4.54; CI=−6.40 to −2.68) than those without diabetes. Patients with diabetes were more likely to have cardiac comorbidities [history of hypertension (OR=3.04; CI=2.19 to 4.22), myocardial infarction (OR=1.55; CI=1.18 to 2.03), heart failure (OR=1.99; CI=1.57 to 2.51)] and neurological comorbidities [history of stroke (OR=1.39; CI=1.03 to 1.87), cognitive impairment (OR=1.75; CI=1.39 to 2.21)]. Conclusions: In the Swiss-AF cohort population, patients with diabetes less often perceived AF symptoms, but had worse quality of life, more cardiac and neurological comorbidities than those without diabetes. These findings have significant clinical implications. The reduced perception of AF symptoms in patients with diabetes might result in a delayed AF diagnosis and consequently more adverse events, especially cardioembolic stroke. This raises the question whether patients with diabetes should be systematically screened for silent AF. Moreover, patients with concomitant AF and diabetes have increased likelihood of comorbidities and therefore deserve more attentive care. Funding Acknowledgement: Type of funding sources: None.